2016
DOI: 10.1097/sap.0000000000000613
|View full text |Cite
|
Sign up to set email alerts
|

The Pacman Perforator-Based V-Y Advancement Flap for Reconstruction of Pressure Sores at Different Locations

Abstract: The V-Y Pacman perforator-based advancement flaps are safe and very effective for reconstruction of pressure sores at various regions. The advantage of our modification procedure include shorter operative time, lesser pedicle dissection, low donor site morbidity, good preservation of muscle, and offers remarkable excursion to the V-Y flap, which make the V-Y Pacman perforator-based flaps an excellent choice for large pressure sore coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The author, in this study, elicits the benefits of SBPBPF over the multiple perforator-based Pacman flaps introduced by Stefano Bonomi. 8 This is the only closely relatable study to the author's current study. This is the first clinical study on the single best perforator-based Pacman flap, and the author showed in this study that the success rate is better than Bonomi et al The age and gender distribution in the Bonomi et al study were comparable to the current author's study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The author, in this study, elicits the benefits of SBPBPF over the multiple perforator-based Pacman flaps introduced by Stefano Bonomi. 8 This is the only closely relatable study to the author's current study. This is the first clinical study on the single best perforator-based Pacman flap, and the author showed in this study that the success rate is better than Bonomi et al The age and gender distribution in the Bonomi et al study were comparable to the current author's study.…”
Section: Discussionmentioning
confidence: 84%
“…Bonomi 8 et al introduced the perforator-based Pacman flap (named so after the shape of the flap) (►Fig. 1) for reconstruction of pressure sores.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of the perforator provides us to dissect the flap base more extensively allowing increased flap mobility (19,20). Furthermore, Bonomi et al (21),suggested that perforator bsed V-Y advancement flap can be designed with Pacman modification to enhance soft tissue coverage for the defect. We preferred perforator based flap in a V-Y advancement design essipecially for cachectic patients and when the donor site laxity did not allow primary closure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] In addition to complete debridement of necrotic tissue and sufficient coverage with healthy tissue, careful selection of flaps for pressure sore reconstruction should be achieved to reduce donor site morbidities and to provide additional opportunities for further surgical reconstruction. [ 1 3 ] Gluteal perforator flaps are the current mainstay of pressure sore reconstruction because of their superiority over conventional musculocutaneous flaps. These superior aspects include the lack of the need to sacrifice the muscles and major vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The V-Y advancement flap is reliable and simple, but its limited mobility is a challenging problem. [ 3 ] The propeller flap is relatively free of flap movement, but vascular compromise due to pedicle twisting or kinking can occur. [ 2 , 9 ] Moreover, flap harvest time is relatively longer because either intra-muscular dissection or skeletonization of the pedicle is often indispensable.…”
Section: Introductionmentioning
confidence: 99%